Islamisasi Ilmu sebagai Model Integrasi dalam Membangun Relasi antara Ilmu dan Agama (Tinjauan Historis-Filosofis) - Munawaroh, Ma'rifatul; Irawan, Vaesol Wahyu Eka (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
Islamization of knowledge emerged when the first world conference was held on Islamic education in Mecca on March 31 to April 8, 1977 with the theme, "Basic for an Islamic Education System". The Islamization of science as one of the integration models is affirmed by Arqom Kuswanjono, that the best model of the relationship between science and religion is an integration model, of course when compared with the other three models, conflict, independence and dialogue. While in the Indonesian context, Mulyadi Kartanegara identified four types of Islamization of the knowledge practiced; integration of science and religion, modernization, "ayatisasi": Islamic Justification of Modern Science, and "Islamic cultivation": Scientification of Islam.